Cervical proprioception accuracy is impaired in patients with axial spondyloarthritis - TONGA, EDA; POLAT, MİNE GÜLDEN; ÖZEN BERKOL, TUĞÇE (ELSEVIER, 2021)
Background: Proprioception is the awareness of body parts and includes joint position sense, kinesthesia, and sense of force. Cervical spine is one of the major affected areas in axial spondyloarthritis (axSpA), and is an essential region for proprioceptive receptors. Objective: To investigate the cervical joint proprioceptive accuracy by using cervical joint positioning error (JPE) method in patients with axSpA and healthy controls. Design: Cross-sectional study. Methods: JPE was calculated for cervical motions in the directions of flexion, extension, rotations, and lateral flexions. Time since diagnosis, symptom duration, spinal mobility, functional status, quality of life, disease activity, and pain were evaluated in axSpA patients. Cervical JPE of axSpA patients was also compared according to radiographic status, biologic use, and existence of cervical syndesmophytes. Results: Eighty-two axSpA patients (52 males) and 71 healthy subjects (53 males) were evaluated. Cervical JPE was higher in patients with axSpA compared to healthy subjects (p < 0.001), except left lateral flexion (p = 0.10). Cervical proprioceptive accuracy for extension and left rotation was better in biologics+ subgroup compared to biologic- subgroup (p < 0.05). No other differences were detected related to radiographic status nor existence of cervical syndesmophytes (p > 0.05). Conclusion: Cervical proprioception accuracy is impaired in patients with axSpA. It seems that controlling disease activity by using appropriate medication may have a positive effect on cervical proprioception accuracy.
Keywords: Spondyloarthritis; Cervical motion; Proprioception